2019
DOI: 10.1108/jsbed-09-2018-0266
|View full text |Cite
|
Sign up to set email alerts
|

Gamification and entrepreneurial intentions

Abstract: Purpose The purpose of this paper is to investigate how gamification can influence entrepreneurial intentions (EI) of a group of users of an online platform provided by a private company. Design/methodology/approach A quantitative research strategy was used with a sample of 220 respondents. These respondents were tested before and after the gamification experience. Findings Main findings support literature suggesting a clear effect of attitudes towards behaviour and perceived behavioural control on EI, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 98 publications
(201 reference statements)
6
40
0
8
Order By: Relevance
“…PBC is the largest contributor to EI training, particularly for students of distance learning in BINUS Online Learning. This work confirms and empirically illustrates the hypothesis of the research by Ruiz-Alba et al (2019) that the gamification learning model evaluated by ATB, PBC, and SN in the TBP definition shapes the desired EI behaviors, although this study does not regulate gender as a mediator. Such findings also lead to further work in the higher education field, in particular in distance education institutions, to the growth of entrepreneurial actions.…”
Section: Resultssupporting
confidence: 85%
“…PBC is the largest contributor to EI training, particularly for students of distance learning in BINUS Online Learning. This work confirms and empirically illustrates the hypothesis of the research by Ruiz-Alba et al (2019) that the gamification learning model evaluated by ATB, PBC, and SN in the TBP definition shapes the desired EI behaviors, although this study does not regulate gender as a mediator. Such findings also lead to further work in the higher education field, in particular in distance education institutions, to the growth of entrepreneurial actions.…”
Section: Resultssupporting
confidence: 85%
“…Based on the demand for innovation and experiential entrepreneurial competencies (Constanţa-Nicoleta et al, 2015 ), game designers simulate a real business environment for learners to run a virtual business (Mennecke et al, 2008 , 2008 ) and avoid risks in the real world so that the cost and uncertainty of being entrepreneurs decrease. Except for general effectiveness (Tasnim, 2013 ), scholars focused on the entrepreneurial mindset, entrepreneurial intention and motivation (Buzady & Almeida, 2019 ; Ruiz-Alba et al, 2019 ), entrepreneurial behavior (Fellnhofer, 2015 ) and entrepreneurial competencies (Williams, 2015 ). Mayer et al ( 2014 ) narrowed the research subjects into engineering students, which showed gaming experience could significantly influence EE.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…Furthermore, Bellotti et al ( 2014 ) analyzed the entrepreneurial mindset of engineering students. In general, the relationship between SGs and entrepreneurship intention and skills is positive (Almeida, 2017 ; Bellotti et al, 2014 ; Buzady & Almeida, 2019 ; Fellnhofer, 2015 ; Ruiz-Alba et al, 2019 ), even long-term positive effectiveness (Kriz & Auchter, 2016 ). However, the study of Newbery et al ( 2016 ) found a significant negative impact for the authentic learning method, perhaps because students understood the complexity of starting a business (Protopsaltis et al, 2013 ).…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…In general, the rationale for utilizing gamification methods in entrepreneurship education relies on Self-Determination Theory principles [37]. In this context, the use of game-like principles and characteristics in learning activities can formulate immersion in a very similar way to games, where participants can learn inductively and make decisions, something that can result in enhancing retention and their creativity [9,38]. Specifically, gamification can engage learners in activities and training scenarios that can stimulate their motivation increase their engagement and most of all enhance their learning interest, experience and knowledge construction.…”
Section: Gamification Game-based Learning and Virtual Reality In Entmentioning
confidence: 99%
“…In the literature, there are some works on gamification and entrepreneurship education, but the adoption of gamification in entrepreneurship education is considered to be quite residual and little has been done on the multidimensional examination of their interrelation and interaction. Indeed, it is pointed out that gamification and entrepreneurial intentions constitute two relevant topics in the business literature that are still lacking empirical investigation [38]. So, the formulation of a concrete framework for entrepreneurship education that will incorporate gamified learning activities and the assessment of their impact on students' entrepreneurship learning and learning experience is highly desired.…”
Section: Gamification Game-based Learning and Virtual Reality In Entmentioning
confidence: 99%